Influence of Wind Speed in Painting Room on the Uniformity of Paint Film - XU Hong - peng, ZOU Hui, WANG Jing - shuai, LI Ding - ding, PANG Mao - fei, ZHANG Mei - rong (Cailiao Baohu, 2021)
The painting process using electrostatic rotating bell - cup is the current mainstream of automotive painting process. In order to ensure that the concentration of VOCs (Volatile Organic Compounds) gas in painting room is lower than its lower explosive limit, an exhaust system will be used to keep the air flowing. In this paper, CFD (Computational Fluid Dynamics) technique was employed to theoretically investigate the effect of wind speed in paint room on uniformity of paint film. Results showed that the uniformity of paint film deteriorated with the increase of wind speed in paint room, and the optimum wind speed range was determined as 0.2～0.4 m/s.